Shotblocker Use in Emergency Care: A Randomized Clinical Trial. (January 2021) - Yildirim, Dilek; Dinçer, Berna
Abstract : This study was conducted to evaluate the effect of ShotBlocker on the intramuscular injection pain and satisfaction in emergency adult patients. This research was designed as a randomized controlled, double-blind, experimental study. The study was conducted with 74 patients who applied to the adult emergency department. Patients were randomized to ShotBlocker and control groups. Patient Assessment Form, Visual Analog Scale, and Visual Analog Patient Satisfaction Scale were used. The mean scores of postinjection pain and satisfaction level were analyzed between the groups; it was determined that while postinjection pain mean score of the experimental group was statistically significantly lower than that of the control group ( p = 0.0001), satisfaction scores were statistically significantly higher in the experimental group than in the control group ( p = 0.004). When the correlation between the intragroup Pain Scores (VAS) and the Satisfaction Scores (VAS) of the groups after injection was examined, a statistically significant and inverse correlation was found ( p < 0.05). It was determined that ShotBlocker was effective in reducing intramuscular injection pain and increasing satisfaction levels.